Leadership 4.0: Navigating the Challenges of the Digital Transformation in Healthcare and Beyond - Georgios Tsekouropoulos; Anastasia Vasileiou; Greta Hoxha; Dimitrios Theocharis; Efthimia Theodoridou; Theodosios Grigoriadis (Administrative Sciences)
The Fourth Industrial Revolution (4IR), characterized by the integration of advanced digital technologies, is transforming industries globally and significantly impacting leadership practices, particularly in the healthcare sector. As organizations adapt to this digital evolution, the demand for effective leadership becomes increasingly critical. This paper explores Leadership 4.0, a framework that identifies the skills and competencies required for successful leadership in the digital age. The study employs a mixed-methods approach, combining a Systematic Literature Review (SLR) with qualitative insights gathered through case studies and the Delphi method, involving healthcare leaders, to investigate leadership practices in organizations undergoing digital transformation. Through case studies and literature reviews, the research seeks to provide a comprehensive understanding of the changing leadership landscape, addressing the unique challenges and opportunities presented by digital transformation in healthcare. The findings indicate that effective Leadership 4.0 requires a combination of digital literacy, strategic foresight, and emotional intelligence. Leaders must exhibit adaptability, drive innovation, and foster a culture of continuous learning to navigate the complexities of digital transformation successfully. The study also emphasizes the importance of internal branding as a critical strategy for aligning employees with the organization’s mission and digital vision, thereby fostering collective commitment to transformation objectives. Key challenges include resistance to change and the ongoing need for upskilling, while opportunities lie in leveraging digital innovations to enhance organizational performance.